Strategi dalam Peningkatan Kepercayaan Diri Remaja Terhadap Pembullying di Rumah Pintar YAFSI - Janiti Kosagi Br Ginting, Gatri; Utama Ritonga, Fajar (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Practicum activities or can be called field work practices (PKL) are one of the courses that must be carried out by prospective social worker students in the Social Welfare Study Program of FISIP USU. This activity is important because it improves skills and implements the theories that have been learned while taking courses that have been offered in the Social Welfare Study Program. The first practicum activity was carried out at the YAFSI Smart House for 2 months.Bullying is a phenomenon that is rampant among adolescents, especially in the school environment. Bullying that is received can be physical, verbal, and relational. Adolescents who get bullying behavior from their friends can affect their self-confidence. Self-confidence is an important psychological factor that affects various aspects of an individual's life, including the ability to face and overcome bullying situations. This study aims to examine the relationship between self-confidence and bullying experiences among adolescents. Nowadays, there are still teenagers or the current generation who lack confidence or are still hesitant in making a decision.